2021
DOI: 10.3390/molecules26123546
|View full text |Cite
|
Sign up to set email alerts
|

Açai (Euterpe oleracea Mart.) Seed Extract Induces ROS Production and Cell Death in MCF-7 Breast Cancer Cell Line

Abstract: Euterpe oleracea Mart. (açai) is a native palm from the Amazon region. There are various chemical constituents of açai with bioactive properties. This study aimed to evaluate the chemical composition and cytotoxic effects of açai seed extract on breast cancer cell line (MCF-7). Global Natural Products Social Molecular Networking (GNPS) was applied to identify chemical compounds present in açai seed extract. LC-MS/MS and molecular networking were employed to detect the phenolic compounds of açai. The antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…The association between mitochondrial dysfunction, generation of ROS, and chromatin changes with autophagy is well reported [33,34], and the ultrastructural changes observed after treatment with E. oleracea indicate a mechanism of action in this sense. Nevertheless, there are reports in line with our results that E. oleracea seed extract induced ROS production and increased mitochondria numbers, suggesting ROS enrollment in autophagy and cell death, possibly by autophagy, which were confirmed by the autophagolysosome formation in the MCF-7 breast cancer cell line [35,36]. Another study demonstrated a reduction in MCF-7 cell viability and death by necroptosis after E. oleracea treatment, revealing that the in vitro mechanism of action still needs enlightenment.…”
Section: Discussionsupporting
confidence: 84%
“…The association between mitochondrial dysfunction, generation of ROS, and chromatin changes with autophagy is well reported [33,34], and the ultrastructural changes observed after treatment with E. oleracea indicate a mechanism of action in this sense. Nevertheless, there are reports in line with our results that E. oleracea seed extract induced ROS production and increased mitochondria numbers, suggesting ROS enrollment in autophagy and cell death, possibly by autophagy, which were confirmed by the autophagolysosome formation in the MCF-7 breast cancer cell line [35,36]. Another study demonstrated a reduction in MCF-7 cell viability and death by necroptosis after E. oleracea treatment, revealing that the in vitro mechanism of action still needs enlightenment.…”
Section: Discussionsupporting
confidence: 84%
“…Numerous pharmacological benefits of açai berry extract and its bioactive components include anti-inflammatory and anti-anxiety properties through modulation of oxidative stress, inflammation, autophagy, and Nrf2 expression in the hippocampus and frontal cortex [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. However, more data are needed to confirm the neuroprotective, anti-inflammatory and antioxidant effect.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is one of the most researched diseases in the world and this fruit has already demonstrated benets against various mechanisms of this disease, such as a positive cytoprotective action for estrogen receptors (MCF-7), chemopreventive potential, effective for cytotoxic effects in breast cancer cell lines, induces autophagy and morphological changes in treated cells, increase mitochondria production aer 24 hours of treatment and reduction of tumor cells (Table 6). [147][148][149][150] Besides cancer, açaí has also been effective in managing obesity, through a positive inuence against pro-inammatory biomarkers, in addition to also being effective against metabolic diseases, such as diabetes, dyslipidemias, inammation, oxidative stress and hypertension. 33 Some of the benets found from açaí against metabolic disorders are the ability of glucose tolerance, insulin resistance, control of lipid metabolism, decreased protein expression of genes involved in lipogenesis and increased expression of transport proteins involved in the excretion of lipids.…”
Section: Açaí (Euterpe Oleracea)mentioning
confidence: 99%